(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث مفهوم الإدارة الاستراتيجية ومكوناتها وأهميتها ومتطلبات تطبيقها والخطوات العلمية والعملية الواجب إتباعها في إدارة استراتيجيات منظمات الأعمال ومعرفة الفروق بينها وبين الخطوات المتبعة في إدارة استراتيجيات منظمات الأعمال الصناعية العامة في الساحل السوري بالإضافة إلى معرفة النتائج المتمخضة عنها. كما تناول البحث مدى توفر متطلبات تطبيق الإدارة الاستراتيجية في تلك المنظمات بالإضافة إلى تبيان العلاقة بين تطبيق مفهوم الإدارة الاستراتيجية والأداء فيها. وقد توصلنا بنتيجة البحث إلى مجموعة من النتائج والمقترحات والتي من المتوقع في حال الأخذ بها العمل على تحسين وتطوير أداء منظمات الأعمال في قطرنا. The research explains strategic management, its component as well as its importance and the requirements of its application. It also shows the scientific and practical steps which should be followed in the management strategies of work organizations, and the knowledge of differences between them and the steps followed in the management strategies of work organizations adopted by The General Industrial Organization of the Syrian Coast. The research also discusses the availability of strategic management requirements in work organizations. At the end, the research reaches a group of important results and suggestions. It is expected to improve and develop the performance of work organizations in our country.